Salmonella Inactivation Model by UV-C Light Treatment in Chicken Breast - Rosa María García-Gimeno; Eva Palomo-Manzano; Guiomar Denisse Posada-Izquierdo (Microorganisms)
This study aims to evaluate the effectiveness of inactivating Salmonella enteritidis in fresh chicken breast by irradiation using a combination of short-wave UV (0, 3, 6, 9, 12, and 15 J/cm2) and a natural antimicrobial such as caffeine (0, 5, 10, 15, and 20 nM/g) at 14 °C as alternative proposals to conventional techniques to reduce pathogens in food. The effect of temperature was studied in an initial phase (2 to 22 °C). The most suitable models were double Weibull in 60% of cases, with an adjustment of R2 0.9903–0.9553, and Weibull + tail in 46.67%, with an adjustment of R2 of 0.9998–0.9981. The most effective combination for the reduction in Salmonella was 12 J/cm2 of UV light and 15 nM/g of caffeine, with a reduction of 6 CFU/g and an inactivation rate of 0.72. The synergistic effect was observed by increasing caffeine and UV light. Furthermore, the physico-chemical characteristics of the food matrix were not affected by the combination of both technologies. Therefore, these results suggest that this combination can be used in the food industry to effectively inactivate Salmonella enteritidis without deteriorating product quality.